Partnership Relations in Handling Export Based Fishery Products : JEL Classification: Q22, Q28, F14, H83, L14 - Herman Herman; Badu Ahmad; Nurdin Nara; Akmal Ibrahim (Newinera Publisher, 2026)
Bone Regency in South Sulawesi is a coastal area with great fishery export potential, especially in tuna, skipjack, cob, and shrimp commodities. However, the dynamics of relations between fisher actors, exporting companies, and the government are still colored by inequality of access to information, dominance of collectors, and weak formal institutions. This condition causes limitations in the competitiveness of export products. This study aims to analyze the form, pattern, and intensity of relationships between actors in handling export fishery products in Bone, as well as identify factors that affect the sustainability of partnerships. The research uses a descriptive qualitative approach with a case study design. Data was collected through in-depth interviews, observations at ports and partner companies, and review of official documents. The informants totaled 17 people representing fishermen, exporting companies, and local government officials. Data analysis was carried out thematically by triangulating sources. Result. The findings show that partnership relationships are divided into formal and informal patterns. Trust-based informal patterns are still dominant at the corporate fishermen level, while formal patterns through MoU, coordination forums, and quality reporting are developing at the corporate government level. However, the limitations of logistics infrastructure, digital literacy, and formal contracts cause fishermen's bargaining position to remain weak. Optimizing resources through technical training, digitizing port services, and strengthening fishermen's cooperatives are considered important to improve transparency, efficiency, and sustainability of the export chain. Synergy between actors with hybrid governance (formal and informal) is key to creating a more inclusive and competitive export partnership.